Tuftsin: A Natural Molecule Against SARS-CoV-2 Infection - Huang, Jiahao; Wang, Jing; Li, Yan; Wang, Ziyuan; Chu, Ming; Wang, Yuedan (Frontiers in Molecular Biosciences, 2022)
Coronavirus disease 2019 (COVID-19) continuously proceeds despite the application of a variety of vaccines. It is still urgent to find effective ways to treat COVID-19. Recent studies indicate that NRP1, an important receptor of the natural peptide tuftsin, facilitates SARS-CoV-2 infection. Importantly, tuftsin is a natural human molecule released from IgG. Here, we found 91 overlapping genes between tuftsin targets and COVID-19-associated genes. Results indicated that tuftsin could also target ACE2 and exert some immune-related functions. Molecular docking results revealed that tustin could combine with ACE2 and NRP1 in stable structures, and their interacted regions covers the binding surfaces of S1-protein with the two receptors. Using surface plasmon resonance (SPR) analysis, we confirmed that tuftsin can bind ACE2 and NRP1 directly. Importantly, tuftsin was verified to effectively impair the binding of SARS-CoV-2 S1-prootein with ACE2 by the SRP-based competition assay. Therefore, tuftsin is an attractive candidate against COVID-19. For the first time, this study demonstrates the utility of human natural peptide has good potency in treating COVID-19. Moreover, given that tuftsin is already contained in existing drugs, results from this study not only provide insight into its action mechanism, but also propose a prompt application of it on COVID-19 patients for assessing its clinical feasibility.